Model Matematika SIK Penyebaran Penyakit Kaki Gajah (Filariasis) - Wellni Praliska; Arnellis Arnellis; Suherman Suherman (Journal of Mathematics UNP, 2019)
Abstrak –The spread of parasitic diseases is a significant threat in the areas of health, social, and economic. One example of the spread of infectious diseases caused by parasites is elephantiasis disease. Elephantiasis disease is an infectious disease caused by filarial worms with the type of Brugaria malayi, Brugaria timori, and Whucereria bancrofti. Elephantiasis disease makes the mosquito as a vector in the spread. To model the spread of the elephantiasis disease (Filariasis), an analysis of the theory that is relevant to the issue is conducted. Furthermore, forming a mathematical model, and then specifying a fixed point and analyse the stability of a fixed point, as well as the interpretation of the results of the analysing of the stability of a fixed point of a mathematical model of the spread of the disease to the elephantiasis disease (Filariasis).Keywords – Mathematics Models, Filariasis, stability theory